Global research trends on the ketogenic diet-gut microbiota relationship: A bibliometric analysis - Manisali, Emre; Ziksahna, Kaan; Adiyil, Rumeysa; Ihlamur, Murat (ELSEVIER SCIENCE INC, 2026)
Introduction: The ketogenic diet (KD) has attracted increasing attention for its potential to modulate the gut microbiota; however, the rapidly expanding literature makes it difficult to identify dominant themes, leading contributors, and research gaps. This study aimed to map global research trends on the KD-gut microbiota relationship using bibliometric methods. Methods: A bibliometric analysis was conducted using the Scopus database. Records published between January 1, 2009 and December 31, 2024 were included (search updated to January 1, 2025). Bibliometric indicators and performance analyses were computed, and keyword co-occurrence and international collaboration networks were visualized using VOSviewer. Results: A total of 404 documents were identified. Publication output increased markedly after 2016 and peaked in 2024, indicating growing scientific interest. The most prolific authors and institutions contributed disproportionately to the field, and thematic mapping revealed five dominant clusters, including neurodegenerative diseases, metabolic regulation, and microbiota-related mechanisms. While the field is expanding, the distribution of document types suggests that conceptual and synthesis work remains prominent. Conclusion: Research on the KD-gut microbiota relationship has grown substantially over the last decade, with clear thematic consolidation around metabolic and neurological outcomes. Future studies should prioritize mechanistic and longitudinal clinical designs and integrate multi-omics approaches to clarify causal pathways and support personalized dietary interventions.
Keywords: Ketogenic diet; Microbiota; Bibliometric analysis; Gut health; Nutrition; Integrative & Complementary Medicine